2015
DOI: 10.1007/s10140-015-1360-3
|View full text |Cite
|
Sign up to set email alerts
|

ED breast cases and other breast emergencies

Abstract: Patients with pathologic processes of the breast commonly present in the Emergency Department (ED). Familiarity with the imaging and management of the most common entities is essential for the radiologist. Additionally, it is important to understand the limitations of ED imaging and management in the acute setting and to recognize when referrals to a specialty breast center are necessary. The goal of this article is to review the clinical presentations, pathophysiology, imaging, and management of emergency bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Its incidence is 0.05%-0.5%. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] PSA is produced by a local trauma generating transmural disruption of the vascular wall and the arterial pressure of the blood cuts up the adjacent tissues, creating a sac that communicates with the lumen of the vessel. This sac is surrounded by 2 layers, the media, and the adventitia.…”
Section: Discussionmentioning
confidence: 99%

Breast pseudoaneurysm: two case reports

Olivares-Antúnez,
Dávila-Zablah,
Garza-Montemayor
2024
MOJCR
“…Its incidence is 0.05%-0.5%. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] PSA is produced by a local trauma generating transmural disruption of the vascular wall and the arterial pressure of the blood cuts up the adjacent tissues, creating a sac that communicates with the lumen of the vessel. This sac is surrounded by 2 layers, the media, and the adventitia.…”
Section: Discussionmentioning
confidence: 99%

Breast pseudoaneurysm: two case reports

Olivares-Antúnez,
Dávila-Zablah,
Garza-Montemayor
2024
MOJCR
“…The differential diagnosis for breast complaints is extensive, from trauma to infection and malignancy. 1,10 Prior literature has shown that breast pain is one of the most common breast complaints. 11,12 This is consistent with our study in patients presenting to the ED where a majority of the patients (57.5%) reported a complaint of breast pain, followed by patients presenting for evaluation of a palpable breast mass.…”
Section: Discussionmentioning
confidence: 99%
“…Use a 22‐gauge needle to inject thrombin at a concentration of 1000 U/mL. Usually a total volume of 0.5 to 1.0 mL is injected at a constant slow rate . Inject directly into the center of the PSA sac, carefully avoiding the PSA neck and underlying artery.…”
Section: Treatmentmentioning
confidence: 99%
“…Usually a total volume of 0.5 to 1.0 mL is injected at a constant slow rate. 3,4,25 Inject directly into the center of the PSA sac, carefully avoiding the PSA neck and underlying artery. Thrombin injection should be avoided in short-neck aneurysms because of the increased risk of thrombosis of the feeding artery.…”
Section: Treatment Option 1: Observation With External Pressure Dressingmentioning
confidence: 99%
See 1 more Smart Citation